Comparative study of regional airports for summing up the competitiveness of Debrecen Airport - Virág, László (Acta Agraria Debreceniensis, 2012)
The Debrecen International Airport in commercial means might be the eastern gate of the European Union. This statement is in question these days .In the neighbouring countries like Slovakia, and Romania the old commercial airports have came through major renovation, and technical improvement. With Romania joining to the Schengen Agreement, Debrecen is going to lose its comparative advantage. So, it is time to follow up what has remained from the five years ago still existing technical and commercial priority of Debrecen aerodrome. In this study looking through the technical background of Kosice, Arad, Cluj-Napoca, Targu-Mures, Oradea, Baia-Mare, Satu-Mare, and Debrecen international airports we have found that Satu-Mare, Arad, and Targu-Mures might be major competitors af Debrecen airport. The level of installed technology has exceeded the one in Debrecen in case of Targu-Mures, and Arad. The situation is the same in Kosice which the absolute market leader in the region.